METAKOGNITION ANALYSIS OF CLASS X SMA NEGERI 5 AMBON IN SOLVING THE SYSTEM PROBLEM OF THREE LINEAR EQUATOINS - Diana Prisillia Huwae; Carolina Selfisina Ayal; Juliana S Molle (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2020)
This study aims to illustrate the activities of grade X students of SMA Negeri 5 Ambon in solving the system problems three variables of linear equations with high, medium and low categories of mathematical abilities. This type of research is quantitative-qualitative. The subject in this study was taken using purposive sampling techniques. The subject in this study was 3 people with 1 person representing each category of mathematical abilities (high, moderate, and low). Research shows that students of grade X SMA N 5 Ambon in solving the system of three variables of linear equations with high category mathematics skills involving knowledge and activity. Subjects involve their activities such as planning, monitoring and evaluation activities. Students of Grade X SMA N 5 Ambon in solving a system of three-variable linear equations in the moderate mathematical category, involving knowledge and activities. Subjects involve their activities such as planning and evaluation activities. However, the subject does not involve monitoring activities. The subject also does not write conclusions from the results obtained. Students of Grade X SMA N 5 Ambon in solving a system of three-variable linear equations in the low mathematics category, involving knowledge and activity. The subject involves only planning activities. Monitoring and evaluation activities are not involved